Are different motivations and social capital score associated with return behaviour among Brazilian voluntary non‐remunerated blood donors?. Issue 4 (28th May 2020) - Estrada, Fernanda G. M. D.; Oliveira, Claudia D. L.; Sabino, Ester C.; Custer, Brian; Gonçalez, Thelma T.; Murphy, Edward L.; Teles, Dahra; Mendrone‐Junior, Alfredo; Witkin, Steve S.; de Almeida‐Neto, Cesar
Summary: Background: We examined the association between social capital score, motivator factors and demographic and donation characteristics and donor return at three Brazilian blood centres in Recife, São Paulo and Belo Horizonte. Material and methods: A total of 5974 donors were interviewed about motivation factors to donate and cognitive and structural social capital just before an effective donation in three Brazilians blood centres in 2009. We assessed the return to a new donation within 2 years for each of these donors. Demographic and donation characteristics, motivators and scores of social capital and their association with donors' return were assessed. Results: Overall, 3123 (52.3%) of the study subjects returned for a blood donation at least once. Predictors of donors' return were male gender (adjusted odds ratio [AOR] = 1.6, 1.3‐1.9, for replacement and AOR = 1.3, 1.2‐1.6, for community donors), previous donation (AOR = 2.7, 2.3‐3.3, for replacement and AOR = 2.9, 2.5‐3.5, for community donors) and high altruism (AOR = 1.3, 1.1‐1.7, for replacement and AOR = 1.2, 1.0‐1.5, for community donors). Altruism was the only motivator associated with return behaviour. Donors from Recife and São Paulo were more likely to return for replacement and/or for community donations than donors from Belo Horizonte. There was no association between social capital score and donor return behaviour. Conclusion: The likelihood to return for a subsequent blood donation is dependent upon characteristics of individual donors and also varies in different regions of Brazil. However, social capital was not associated with the likelihood of return behaviour. A better understanding of altruistic categories and appeals may help to improve donor recruitment and retention.